Maintenance priority towards the features and facilities in Malaysian public parks: Visitors’ perspective versus actual experience - Cheong Peng Au-Yong, Cheong Peng Au-Yong; Xing Ni Gan, Xing Ni Gan; Azmi, Nur Farhana; Zainol, Rosilawati; Mat Radzuan, Indera Syahrul (ASEJ, 2023)
The potential of public parks being able to promote mental and physical health of the public is widely discussed in recent years. However, the report for public park issues becomes a norm too. One of the issues being debated is the maintenance drawback in Malaysian public parks, implicating underutilisation of the parks. To address the issue, this paper aims to examine the maintenance priority towards public park’s features and facilities in Malaysia by considering the park visitors’ expectation and demand. A questionnaire survey was distributed to the park users and visitors with 1658 valid questionnaire responses. A mean analysis was performed to rank the maintenance of park features and facilities in both visitors’ perspective and actual experience. Subsequently, Wilcoxon signed-rank test was deployed to examine the difference between visitors’ perspective and actual experience towards maintenance of the park features and facilities. The findings determine ten park features and facilities that should be prioritised in respect to their maintenance. Furthermore, it is proven that significant difference occurs between visitors’ perspective and actual experience towards all park features and facilities. As a result, the study confirms the need of improving the park maintenance process and recommends the introduction of maintenance prioritisation towards the park features and facilities.